2016
DOI: 10.1167/iovs.16-20446
|View full text |Cite
|
Sign up to set email alerts
|

The Effect on Retinal Structure and Function of 15 Specific ABCA4 Mutations: A Detailed Examination of 82 Hemizygous Patients

Abstract: In the hemizygous state, 2/15 ABCA4 alleles retain preserved peripheral retinal function; 7/15 are associated with either preserved or only mildly abnormal retinal function, worse in older patients; 6/15 behave like null mutations. These data help characterize the degree of dysfunction conferred by specific mutant ABCA4 proteins in the human retina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(78 citation statements)
references
References 36 publications
15
63
0
Order By: Relevance
“…S3), although the BVCA was 0.05 logMAR units bilaterally. This may be because the preserved foveal region was too small to evoke normal ERGs, and we suggest that the etiology of our three cases was similar to that reported by Kondo et al 44 A sparing of the fovea is commonly observed in different types of macular diseases, such as in ABCA4-and PRPH2associated retinopathies, 17,18,43,[45][46][47][48] mitochondrial retinal dystrophy, 49 macular dystrophy with CRB1 mutation, 50 and agerelated macular degeneration. [51][52][53][54] The explanations for the physiologic and anatomic sparing of the fovea have been presented in many publications.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…S3), although the BVCA was 0.05 logMAR units bilaterally. This may be because the preserved foveal region was too small to evoke normal ERGs, and we suggest that the etiology of our three cases was similar to that reported by Kondo et al 44 A sparing of the fovea is commonly observed in different types of macular diseases, such as in ABCA4-and PRPH2associated retinopathies, 17,18,43,[45][46][47][48] mitochondrial retinal dystrophy, 49 macular dystrophy with CRB1 mutation, 50 and agerelated macular degeneration. [51][52][53][54] The explanations for the physiologic and anatomic sparing of the fovea have been presented in many publications.…”
Section: Discussionsupporting
confidence: 80%
“…These FAF abnormalities, however, were much less severe than in other macular dystrophies. 2,7,10,11,13,15,17,21,23,24,[41][42][43] Also, a hypo-AF, which indicates long-term RPE dysfunction, was not observed in any of the eyes. By comparing the FAF of a severe case with CRX-retinopathy that had severe photoreceptor and RPE degeneration at the macula, we would strongly suggest that patients with POC1B-associated retinopathy had never had severe hyporeflectivity, as found in patients with CRX-retinopathy.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The age of onset for individuals homozygous for this variant ranges from 10 to 26 years with an average age of 19 yr (Fingert, Eliason et al 2006, Cideciyan, Swider et al 2009, Hwang, Zernant et al 2009, Tanna, Strauss et al 2017. This age of onset is consistent with the moderate disease classification presented here and the moderate classification based on clinical findings (Fakin, Robson et al 2016). When this mutation is in trans with the S1696N mutation, reported here to be a mild Class 3 mutation, then the age of onset is increased to 45 yr supporting our Class 3 designation of the S1696N variant (Hwang, Zernant et al 2009).…”
Section: Discussionsupporting
confidence: 86%
“…Thus, some of the asymptomatic family members without detailed examinations could have been misclassified to be normal although other factors such as ethnic and environmental differences in the presence of photoreceptor abnormality should be considered to explain the low penetrance in the other studies. 9 A sparing of the fovea is commonly observed in different types of macular diseases, such as in ABCA4-and PRPH2related retinopathies, [27][28][29][30][31][32][33] mitochondrial retinal dystrophy, 34 macular dystrophy with CRB1 mutation, 35 and age-related macular degeneration. [36][37][38][39] The explanations for the physiologic and anatomic sparing of the fovea have been presented in many publications.…”
Section: Discussionmentioning
confidence: 99%